Film Industry at the Service of EU Identity Politics - E. V. Khakhalkina; A. V. Vyachistaya (Vestnik MGIMO-Universiteta)
Mass cinema can act as a powerful tool for influencing public opinion by appealing to shared values and collective historical memory, while simultaneously constructing and guiding these elements in alignment with policy objectives. This article explores the thesis that national cinema, as an element of a common cultural code, plays a significant role in the formation and reinforcement of collective (socio-cultural) identity. Specifically, it examines the significance of Brussels' efforts to cultivate a robust film industry as part of the European Union's strategy for constructing a collective identity.The authors test the hypothesis that cinema serves as a medium for fostering a sense of belonging and emotional connection among EU citizens. To this end, the study aims to uncover the specific mechanisms by which common historical and social narratives are conveyed through European Union cinema. The research methodology is grounded in a structuralist perspective on cinema (P. Wallen, C. Metz).The article analyzes how the EU has intensified its institutional support and promotion of European cinema, particularly in response to the «crisis of ideas» in Hollywood, which has left a void in the global film market. This analysis is contextualized within the broader sociopolitical landscape, including the rising popularity of mass cinema during the pandemic and the heightened urgency for strengthening EU collective identity amid the Ukrainian crisis and the initiation of a special military operation.The findings indicate that the EU is increasingly leveraging the film industry to disseminate narratives, ideas, and values critical for both situational objectives – such as consolidating public opinion on specific political issues (illustrated by the «militarization» of the film market in response to the 2022 military operation) – and long-term goals of fortifying the EU's collective identity. However, the long-term efficacy of cinema in shaping public opinion is constrained by its susceptibility to rapid trend shifts driven by audience preferences.